Vestibular Function Measurement Devices - Miles, Richard D.; Zapala, David A. (Seminars in Hearing, 2015)
Vestibular function laboratories utilize a multitude of diagnostic instruments to evaluate a dizzy patient. Caloric irrigators, oculomotor stimuli, and rotational chairs produce a stimulus whose accuracy is required for the patient response to be accurate. Careful attention to everything from cleanliness of equipment to threshold adjustments determine on a daily basis if patient data are going to be correct and useful. Instrumentation specifications that change with time such as speed and temperature must periodically be checked using calibrated instruments.
Keywords: Vestibular; eye-tracking; vestibular ocular reflex; visual angle; caloric